The Effect of Benefits, Trust, Convenience, And Risk on Interest in Using Mobile Banking (Empirical Study on the Community of Sukoharjo Regency) - Alam, Agev Fefy Bena; Witono, Banu (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of perceived benefits, trust, ease of use, and perceived risk on the intention to use mobile banking in Sukoharjo Regency. Using purposive convenience sampling, a quantitative causal method was employed, with data collected via questionnaires from bank customers aged 18–45 from BRI, BNI, BSI, BCA, and Mandiri. While this approach offers initial insights, the use of online Google Forms may exclude individuals with limited digital access, potentially reducing the external validity of the findings. Results show that perceived benefits and ease of use have a significant positive impact on usage intention, highlighting the practical value and user-friendliness of mobile banking platforms. Surprisingly, perceived risk also has a positive effect, possibly indicating that users are more cautious and actively utilize security features. This interpretation would benefit from stronger theoretical support or qualitative data. Meanwhile, trust in security and privacy does not significantly influence intention, which may suggest that digital trust is now a normative expectation. However, alternative explanations, such as users’ limited awareness of security mechanisms, should also be considered. Future research is encouraged to adopt a mixed-methods approach and apply stratified random sampling to enhance representativeness and gain deeper insights into user motivations, especially concerning risk perception and digital trust.